Midwives' Coping Strategies After Failure to Assist in the Delivery Process - Muhammad Syam Ilham; Asniar Khumas (PSPP JOURNALS, 2026)
Failure in assisting childbirth is a difficult professional experience that may create psychological pressure for midwives, especially when the incident results in maternal or infant death. Such failure is not only understood as a clinical event, but also as an emotional and moral burden that can lead to sadness, guilt, anxiety, fear, self blame, and trauma. This study aimed to explore the coping strategies used by midwives after experiencing failure in assisting the childbirth process. A qualitative approach with a case study design was employed to obtain an in depth understanding of the participants’ subjective experiences. The study involved two midwives who had directly experienced failure in assisting childbirth. Data were collected through semi structured interviews and analyzed using qualitative descriptive analysis by identifying important statements, grouping similar meanings, and developing themes related to coping strategies. The findings show that the participants predominantly used emotion focused coping rather than problem focused coping. The main coping strategies included self control through daily activities, positive reappraisal through religious meaning, and social support from family and coworkers. Self control helped the participants manage disturbing thoughts and emotional tension. Religious reappraisal helped them interpret the painful experience through acceptance and surrender to Allah SWT. Social support provided emotional reassurance, professional validation, and a sense of not being alone. These strategies helped the midwives reduce psychological distress, rebuild emotional stability, and continue their professional responsibilities. The study suggests that coping after childbirth failure should not be viewed only as an individual process, because midwives also need supportive professional environments, including peer support, emotional debriefing, and institutional attention to psychological well being after adverse childbirth events.